Does addition of glucocorticoids to the initial therapy influence the later course of the disease in patients with early RA? Results from the Swiss prospective observational registry (SCQM). Issue 1 (January 2017) - Mueller, Ruediger; Reshiti, Nazim; Kaegi, Toni; Finckh, Axel; Haile, Sarah; Schulze-Koops, Hendrik; Schiff, Michael; Spaeth, Michael; Kempis, Johannes
Abstract The main goal of this study was to analyse whether initial addition of glucocorticoid to DMARD therapy influences the long-term course of the disease in patients with early rheumatoid arthritis. All patients from the Swiss RA cohort SCQM with recent-onset arthritis (disease duration ≤1 year) were analysed. The exposure of interest was the use of glucocorticoids (GCs) at baseline. As primary outcome, we considered clinical and radiographic disease progression, assessed by the disease activity (disease activity score, DAS-28), function (health assessment questionnaire disability index, HAQ-DI) and structural joint damage (Ratingen erosion score). The baseline disease characteristics were compared using standard descriptive statistics. The effects of initial GC use on disease progression during follow-up were estimated using linear mixed models with random slope and random intercept, adjusted for potential confounders. In total, 592 patients with early disease were available, with 4.3 years of follow-up (average). Of these, 363 were initially treated with glucocorticoids (GC patients) and 228 were not (no-GC patients). DAS-28 (4.6 vs. 4.3, p  = 0.01) and the HAQ-DI (0.94 vs. 0.82, p  = 0.01) were higher at baseline in GC patients, while other prognostic factors were balanced at baseline. Neither the change of DAS-28, of HAQ-DI nor of the development of joint erosions differed between the two groups during follow-up. Escalation of treatment employing biologics was documented in 18.0% of the no-GC patients and 27.3% of the GC patients (p  < 0.01). In this cohort, patients with early RA initially treated with GCs had higher measures of disease activity at baseline in comparison to no-GC patients. Despite a similar course of the disease in GC versus non-GC patients, the higher escalation rate to biologic agents in GC patients may reflect a disease less responsive to therapy in these patients. These data suggest that GC use as part of the initial therapeutic strategy in early RA may prevent a more severe course of the disease in patients with higher clinical disease measures at the start of therapy.